ChemInform Abstract: Silicon‐Induced Phenanthrene Formation from Benzynes and Allenylsilanes. Issue 41 (19th September 2013) - Hwu, Jih Ru; Swain, Sharada P.
Abstract The new mild and high regioselective silicon‐induced reaction proceeds through a [2 + 2 + 2] pathway without a catalyst.